2023
DOI: 10.3389/fpsyt.2022.1090149
|View full text |Cite
|
Sign up to set email alerts
|

Pre-operative administration of butorphanol mitigates emergence agitation in patients undergoing functional endoscopic sinus surgery: A randomized controlled clinical trial

Abstract: BackgroundThis study explored the effectiveness of pre-operative intravenous injection of butorphanol in the alleviation of emergence agitation (EA) in patients undergoing functional endoscopic sinus surgery (FESS).MethodsPatients (n = 708) were randomized into two groups. The butorphanol group (Group B, n = 358) received butorphanol infusion (20 ug/kg) before anesthesia induction, while the control group (Group C, n = 350) received an equal volume of normal saline infusion. General anesthesia was induced with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Here, an initial dose of butorphanol 6-10 µg/kg/h was used, which is lower than the recommended dose of 10-20 µg/kg/h in previous studies [16]. Our results demonstrated that a lower dose of butorphanol can provide a similar analgesic effect to that of morphine [17], while reducing the risk of nausea, respiratory depression, and drowsiness.…”
Section: Discussionmentioning
confidence: 61%
“…Here, an initial dose of butorphanol 6-10 µg/kg/h was used, which is lower than the recommended dose of 10-20 µg/kg/h in previous studies [16]. Our results demonstrated that a lower dose of butorphanol can provide a similar analgesic effect to that of morphine [17], while reducing the risk of nausea, respiratory depression, and drowsiness.…”
Section: Discussionmentioning
confidence: 61%
“…This stability in MAP is consistent with existing literature highlighting effectiveness of beta blockers in maintaining intra-op hemodynamic stability. 18 Notably, heart rate differences were significant, especially post-medication and intraoperatively. The bisoprolol group exhibited a higher heart rate, averaging 92.47 bpm±5.8 post-medication and 93.77 bpm±5.8 intra-operatively, compared to the placebo group's 63.41 bpm±4.8 and 62.16 bpm±4.3, respectively.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20][21] In addition, butorphanol has also been proven to mitigate emergence agitation and reduce postoperative shivering. 22,23 Clinical practice concerning pair-wise combinations of butorphanol with ketorolac or dexmedetomidine via patient controlled intravenous analgesia (PCIA) has been well-established recently, while the beneficial characteristic and related side effects of butorphanol in combination with ketorolac and dexmedetomidine together in postoperative multimodal analgesic strategies remain to be verified in large clinical practice. 24 This retrospective study aims to investigate the efficacy and safety of butorphanol combined with dexmedetomidine and ketorolac in multimodal analgesia after hepatobiliary surgery as compared with sufentanil.…”
Section: Introductionmentioning
confidence: 99%